The effect of Nigella sativa on inflammation-induced myocardial fibrosis in male rats - Fatemeh Norouzi; Azam Abareshi; Fereshteh Asgharzadeh; Farimah Beheshti; Mahmoud Hosseini; Mehdi Farzadnia; Majid Khazaei (Wolters Kluwer Medknow Publications, 2017)
Nigella sativa (NS) (Ranunculaceae) used as a protective and therapeutic traditional medicine. This study evaluates the effect of NS on inflammation-induced myocardial fibrosis, serum and tissue inflammatory markers, and oxidative stress status in male rats. Fifty male Wistar rats were divided into five groups: (1) control; (2) lipopolysaccharide (LPS), 1 mg/kg/day; (3) LPS + NS (hydroalcoholic extract), 100 mg/kg/day; (4) LPS + NS, 200 mg/kg/day; (5) LPS + NS, 400 mg/kg/day (n = 10 in each group). The duration of LPS administration was two weeks. At the end of the experiment, blood samples were taken and ventricles were homogenized and stained for histological evaluation. Serum nitrite levels were lower in LPS group than the control group (22.98 ± 1.03 vs 28.5 ± 0.93 μmol/L), in which they were significantly increased by NS treatment (P < 0.05). Higher levels of heart interlukine-6 (IL-6) and tumor necrosis factor-α (TNF-α) were observed in LPS group compared to the controls (IL-6: 6805 ± 656 vs 4733 ± 691 pg/mL; TNF-α: 6504 ± 501 vs 5309 ± 452 pg/mL), in which they were reduced by NS 400 mg/kg compared to LPS groups (P < 0.05). A significant increment of malondialdehyde and reduction in heart total thiol, superoxide dismutase and catalase concentrations were observed in LPS group (p < 0.05) which significantly restored with treatment by three doses of NS. Histopathological studies showed higher inflammatory cell infiltrates, cardiac fibrosis, and collagen deposition in LPS group, which were reduced by the administration of NS. Treatment by NS reduced myocardial fibrosis in inflammation-induced fibrosis, possibly through improving oxidative/anti-oxidative balance.